Effect of Ramadan Fasting on Anthropometric Measures and Metabolic Profiles among Type 2 Diabetic Subjects (Journal of Enam Medical College, 2015)
Background: Fasting from dawn to dusk during the month of Holy Ramadan is obligatory for all healthy adult Muslims. Individuals are exempted from fasting if they are suffering from an illness that could be adversely affected by fasting. Although The Quran exempts sick people from fasting, many Muslim diabetic patients may not perceive themselves as sick and are keenly interested to fast. But they fast without proper medical guidance exposing themselves to certain risks as a direct consequence of fasting. So we designed this study to assess the impact of fasting during Ramadan and to evaluate the effects of fasting on their biochemical profiles in patients with diabetes.Objective: The objective of this study was to investigate whether Ramadan fasting has any effect on body weight, blood pressure, fasting glucose, HbA1C, serum lipids, serum creatinine among type 2 diabetic patients.Materials and Methods: Fifty two stable outpatients with type 2 diabetes with intention to fast were studied in the month of Ramadan 1434 Hijri calendar year (11th July to 9th August, 2013) at two points of time: one week before Ramadan (visit 1) and within last 3 days before the end of Ramadan (visit 2). During each visit the height, body weight and blood pressure were recorded. Blood samples were collected for fasting glucose, HbA1C, total cholesterol, triglyceride, high density and low density lipoprotein cholesterol and creatinine. Data were analyzed by Students paired t-test using SPSS system and results were expressed as mean ± SD. Probability values were considered to be significant if it was less than 0.05.Results: There were 30 (62.8%) males and 22 (37.2%) females with a mean age of 54.7 ± 11.55 (range 3580) years and mean duration of diabetes was 5.5 ± 5.2 years (range 9 months18 years). In this study mean weight of the patients decreased significantly from 60.5 ± 12.6 kg to 58.5 ± 11.3 kg (p